Detection of Pseudomonas aeruginosa in Hospital Contamination (Baghdad Science Journal, 2025)
The Present investigation includes the isolation and identification of Pseudomonas aeruginosa for different cases of hospital contamination from 1/ 6/2003 to 30/9/2004, the identification of bacteria depended on morphological , cultural and biochemical characters, 37 of isolates were diagnosed from 70 smears from wounds and burns beside 25 isolates were identified from 200 smears taken from operation theater and hospital wards including the floors , walls , sources of light and operation equipment the sensitivity of all isolates to antibiotic were done , which exhibited complete sensitivity to Ciprofloxacin , Ceftraixon, Tobromycin and Gentamysin ,while they were complete resist to Amoxcillin , Tetracyclin , Nitrofurantion , Clindamycin Cefotoxam and Methoprim.